Comparative Study of Plasma Nitriding for Dental Implant with or Without Thermocycling - Nitesh Kumar; Rohit Sharma; Rushikesh R. Mahaparale; Lishoy W. Rodrigues; Akhil Rao; Ravi Joshi (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: PN is a cutting-edge method for enhancing the surface hardness and corrosion resistance of metallic components. Aim: To compare and assess the effect of PN on the surface lubrication (SL) and surface topography (ST) of different DI-AS with and without thermocycling (TC). Material and Method: 52 I- AS were surface treated with PN, The samples were divided into2 groups i.e. Group A (GIS) and Group B (BIS) 26 samples each with and without TC. Results: Intergroup and intragroup comparison of RT and SR showed significant differnces, with Group A1 having higher values than Group B1, and Group A2 showing a similar trend over Group B2. Conclusion: TC replicates stressors, but it differs from real-life conditions seen in the human oral cavity.